(untitled) (International Journal of Nursing Education, 2020)
This study is a quasi-intervention investigation to examine the result of the participatory learning programof pre-retirement on personal satisfaction with older adults’. The participants were 120 older adults livingin cities and rural areas selected by purposive sampling technique. The sample group is divided into 2groups: urban and rural groups, intervention and control group of thirty each group. The intervention wasconducted for 12th weeks to improve readiness aging and personal satisfaction as measured by demographyquestionnaire, pre-retirement survey form, and personal satisfaction form assessment parameter. Dataon pre-retirement and personal satisfaction were collected before and after a 12th-week participatorylearning program of pre-retirement. Participants in the control group received the convention care. Therewere significant differences between the two groups on autonomous regulation. There was no significantdifference found in the pretest mean value base on pre-retirement in both groups. The posttest mean valuesof the pre-retirement and personal satisfaction were significantly higher than those of the control group.There was a significant difference between groups (p<.001).The results of the study have shown that a participatory-learning program is effective in pre-retirement andpersonal satisfaction. It would improve the successful aging and quality of life in a long later life.